Web objects ambient: An integrated platform supporting new kinds of personal web experiences - Firmenich, Sergio Damian (2016)
The Personal Web arose to empower end users with the ability to drive and integrate the Web by themselves, according to their own interests. This is usually achieved through Web Augmentation, Mashups or Personal Information Managers (PIM), but despite the diversity of approaches, there are still scenarios that require to be solved through the combination of their features, which implies the end user knowing diverse tools and being able to coordinate them. This paper presents WOA, a platform conceived under the foundations of the Personal Web for supporting the harvesting and materialization of information objects from existing Web content, and their enhancement through the addition of specialized behaviour. This makes it possible to conceive multiple Web information objects coexisting in a same space of information and offering the end user with different modes of interaction, therefore, with multiple kinds of personal Web experiences.